Answer:
1655
Step-by-step explanation:
Note the common difference d between consecutive terms of the sequence
d = - 1 - (- 4) = 2 - (- 1) = 5 - 2 = 8 - 5 = 3
This indicates the sequence is arithmetic with sum to n terms
=
[ 2a₁ + (n - 1)d ]
Here a₁ = - 4, d = 3 and n = 90, thus
=
[ (2 × - 4) + (89 × 3) ] = 45(- 8 + 267) = 45 × 259 = 1655
Answer:
it changed 21 Fahrenheit
Step-by-step explanation:
-14.8 - 6.2 = -21
and minus + minus = +
so, -14.8 + 21 = 6.2
i think so that is the right answer
2!!! I better get 5 points
34-5x+2(x-2)=15 1st get rid of () by distributing the 2.
34-5x+2x-4=15 Now collect like terms.
30-3x=15 Get -3x by itself by subtracting 30 in both sides.
-3x=-15 You want X by itself so divide by -3 on both sides.
x=5
⇒ common ratio =r=3 and the given sequence is geometric sequence. Where an is the nth term, a is the first term and n is the number of terms. ⇒ 12th term is 708588 .
(May be wrong for some other users, although it's correct for me.)